Composição e estrutura de comunidade de peixes em diferentes praias da Baía de Todos os Santos, Bahia, Brasil - Duarte, Luiz Alberto de Góes (2013)
A year-long otter trawl survey in the Todos os Santos bay (TSB) was conducted between November 2011 and September 2012 with the aim of describing the composition and structure of fish communities of the bay and check community fluctuations in both periods of the hydrological cycle (dry and wet). Fifty-three morphospecies were catch, comprising 10 orders and 29 families. The most representative families in terms of species richness were, respectively, Carangidae, Gerreidae, Syngnathidae, Engraulidae, Gobiidae and Paralichthyidae. Despite the significant number of species caught, the fish community of the Todos os Santos bay, on the beaches sampled with trawl, is dominated by five species: Atherinella brasiliensis, Sphoeroides greeleyi, Eucinostomus argenteus, Sphoeroides testudineus and Lile piquitinga, which represent 99.5% of the relative importance of the catch. Influences of environmental parameters of rainfall, temperature and salinity on the composition and structure of fish fauna of TSB were absent or very subtle. The use of different fishing gear (simple net and with bag) did not influence the values of CPUE for different beaches sampled. We can conclude that the shallow areas of the Todos os Santos bay have quite important for maintaining their fish stocks, since species (including commercial interest) to use, partially or completely, the TSB as nursery or creation area.